Photonics devices : design, fabrication, and experiment - He, Yue. (2009)
Conventional optical waveguides based on either index or interference guiding pose a challenge, because a high index core cannot guide effectively as its dimensions scale down – the power in that case being largely transmitted in the cladding. Recently, guiding light in a nanometer core is possible by creating a large discontinuity of electric field at the high/low index interface. We propose a nanometer-scale air core embedded in silicon demonstrating superior optical confinement and approximate a solution with Marcatili’s method. We study the power confinement, intensity, and parametric dependency using FDTD for two polarizations (Quasi-TE and Quasi-TM). Optical confinement is 28% higher compared to that of slot waveguides and the core intensity per µm2 is 95% higher than in the silicon region. An investigation on potential applications of the proposed waveguide structure, with different core active material choices was also conducted in this report, suggesting high performance amplitude modulator can be made based on the electro-optical polymer and our novel embedded core waveguide.